Elementary Row Operations Interchange two equations Multiply one equation by a nonzero constant Add a multple of one equation to another equation.

Slides:



Advertisements
Similar presentations
Matrices. Special Matrices Matrix Addition and Subtraction Example.
Advertisements

Solving Equations Algebra Tiles.
8.3 Solving Systems of Linear Equations by Elimination
3.2 Solving Systems Algebraically 2. Solving Systems by Elimination.
Solving System of Linear Equations. 1. Diagonal Form of a System of Equations 2. Elementary Row Operations 3. Elementary Row Operation 1 4. Elementary.
3-2: Solving Linear Systems
Solve each with substitution. 2x+y = 6 y = -3x+5 3x+4y=4 y=-3x- 3
Drill Solve the linear system by substitution. 1.y = 6x – 11 -2x – 3y = x + y = 6 -5x – y = 21.
3.2 Solving Systems of Equations Algebraically Substitution Method Elimination Method.
Solving Systems of Linear Equations
Solving Systems of Equations
Math 201 for Management Students
How To Find The Reduced Row Echelon Form. Reduced Row Echelon Form A matrix is said to be in reduced row echelon form provided it satisfies the following.
Do Now 1/13/12  In your notebook, list the possible ways to solve a linear system. Then solve the following systems. 5x + 6y = 50 -x + 6y = 26 -8y + 6x.
Integrated Math 2 Lesson #7 Systems of Equations - Elimination Mrs. Goodman.
6-3: Solving systems Using Elimination
Elimination Link to video. Example: Find the P.O.I. by elimination for and Steps Example 1a. Rearrange one (or both) of the equations so that the x’s.
Solving Linear Systems by Elimination Math Tech II Everette Keller.
Solve Systems of Linear Equations Using Elimination Honors Math – Grade 8.
Solving Systems of Linear Equations by Elimination Solve linear systems by elimination. Multiply when using the elimination method. Use an alternative.
Bell Ringer 2x – 3y = 4 5x + 3y = 10. HW Check Check elimination part 1 practice.
MFM 2P Minds On Add or Subtract the following equations in order to make “y” equal 0.
SOLVING SYSTEMS ALGEBRAICALLY SECTION 3-2. SOLVING BY SUBSTITUTION 1) 3x + 4y = 12 STEP 1 : SOLVE ONE EQUATION FOR ONE OF THE VARIABLES 2) 2x + y = 10.
Matrices and Systems of Equations
Chapter 4 Section 3. Objectives 1 Copyright © 2012, 2008, 2004 Pearson Education, Inc. Solving Systems of Linear Equations by Elimination Solve linear.
Slide Copyright © 2008 Pearson Education, Inc. Publishing as Pearson Addison-Wesley A set of equations is called a system of equations. The solution.
Solving Linear Systems By Elimination. Solving Linear Systems There are three methods for solving a system of equations: By Graphing them and looking.
7.4. 5x + 2y = 16 5x + 2y = 16 3x – 4y = 20 3x – 4y = 20 In this linear system neither variable can be eliminated by adding the equations. In this linear.
Do Now (3x + y) – (2x + y) 4(2x + 3y) – (8x – y)
Bell Ringer: Combine like terms 1)4x + (-7x) = 2)-6y + 6y = 3)-5 – (-5) = 4)8 – (-8) =
MAT111 epw 11/1/061 ALGEBRA REVIEW Three Basic Rules.
SOLVING SYSTEMS USING ELIMINATION 6-3. Solve the linear system using elimination. 5x – 6y = -32 3x + 6y = 48 (2, 7)
Section 7-3 Solve Systems by Elimination SPI 23D: select the system of equations that could be used to solve a given real-world problem Objective: Solve.
Multiply one equation, then add
Elimination using Multiplication Honors Math – Grade 8.
Adding two numbers together which have the same absolute value but are opposite in sign results in a value of zero. This same principle can be applied.
Multivariable linear systems.  The following system is said to be in row-echelon form, which means that it has a “stair-step” pattern with leading coefficients.
3-2: Solving Linear Systems. Solving Linear Systems There are two methods of solving a system of equations algebraically: Elimination Substitution.
Chapter 5: Systems of Linear Equations Section 5.1: Solving Systems of Linear Equations by Elimination.
WARM-UP. SYSTEMS OF EQUATIONS: ELIMINATION 1)Rewrite each equation in standard form, eliminating fraction coefficients. 2)If necessary, multiply one.
Lesson 7-3 Solving Linear Systems of Equations using Elimination.
Elimination Method - Systems. Elimination Method  With the elimination method, you create like terms that add to zero.
College Algebra Chapter 6 Matrices and Determinants and Applications
Solve Linear Systems By Multiplying First
6) x + 2y = 2 x – 4y = 14.
10.3 Solving Linear Systems
Solving Systems of Equations using Elimination
Solve Systems of Equations by Elimination
Solving Systems of Linear Equations in 3 Variables.
Solve for variable 3x = 6 7x = -21
3-2: Solving Linear Systems
6-2 Solving Systems Using Substitution
6-3 Solving Systems Using Elimination
Solving Systems Using Elimination
REVIEW: Solving Linear Systems by Elimination
Solve Systems of Equations by Elimination
Solve Linear Equations by Elimination
Objectives Solve systems of linear equations in two variables by elimination. Compare and choose an appropriate method for solving systems of linear equations.
Solving Linear Equations
3-2: Solving Linear Systems
Simultaneous Equations starter
7.3 Notes.
Solving a System of Equations in Two Variables by the Addition Method
Solving Systems of Linear Equations in 3 Variables.
Warm Up 12/3/2018 Solve by substitution.
6.3 Using Elimination to Solve Systems
3-2: Solving Linear Systems
3-2: Solving Linear Systems
Solving Systems by ELIMINATION
Solving Linear Equations
Presentation transcript:

Elementary Row Operations Interchange two equations Multiply one equation by a nonzero constant Add a multple of one equation to another equation

Equation Properties Must be of the first degree (linear equation) Must be of the form ax+by+cz=h If solving for (n) variables, must have (n) equations.

2y + 2x + 2z = 0 2x + 4z - 4y = 8 Process of Elimination We have three equations and we are solving for three unknowns (x, y, and z) -2z + 4y + 2x = 4

Setting Up For Elimination Of the equation, ax+by+cz=h, (where a, b, c, and h are known, and x, y, and z are unknown) the unknown variables must be placed under the same column

Example of Setting Up For Elimination 2y + 2x + 2z = 2 2x + 4z + 4y = 8 -2z + 4y + 2x = 4 2x + 2y + 2z = 0 2x - 4y + 4z = 8 2x + 4y - 2z = 4 Green is original equation. Blue is set up equation. X YZH

Rules for Elimination After setting up the equations in the form previously shown, decide which variable will be the first to be reduced to zero

Subtract the first equation from the last equation. (This way it is the x variable that reduces to a value of zero.) 2x + 4y – 2z = 4 -2x – 2y – 2z = 0 2y – 4z = 4 The first two equations are the same as the original, but the last equation has been modified in order to reduce the number of unknowns. 2x + 2y + 2z = 0 2x – 4y + 4z = 8 2y – 4z = 4

Rules for Elimination We have now two equations with three unknown variables and one with two unknowns. Next step is to reduce another two equations to produce another equation with two unknowns.

We’re going to get rid of another term by subtracting the first from the second. 2x – 4y + 4z = 8 - 2x – 2y – 2z = 0 -6y + 2z = 8 The first equation is the same, but the second and third equations now have two unknowns. 2x + 2y +2z = 0 - 6y + 2z = 8 2y – 4z = 4

Rules for Elimination With two equations and two unknowns, we can figure a way to reduce them to have one equation, one unknown. We do this in the following way:

To get rid of one of the unknowns on either the second or the third equation we multiply the third equation by 3, this way they both have the same coefficient in front of the variable(y) we are reducing 3 (2y – 4z = 4) -6y+ 2z = 8 The result after multiplying by three is : 6y – 12z = 12 -6y+ 2z = 8 Now we add the second equation to the third to approach an equation with one unknown. 6y – 12z =12 + (-6y + 2z = 8) -10z = 20 Note: The bottom equation can be multiplied by two if the (z) variable was to be reduce.

Rules for Elimination We now are set to solve for the variables.

The equations that we are left with are: 2x + 2y + 2z = 0 - 6y + 2z = z = 20 We can solve for the third term because its one equation one unknown.( A simple use of algebra results in the following result.) z = -2 We can use the value for z and use it to in the second equation to make it into one equation one unknown.( With the use of substitution leads to the following equation.) -6y – 4 = 8 Solving for the variable that is unknown leads to: y = -2

The last step is to use the values that have previously been solved for (y and z) to make the first equation into one equation one unknown. 2x – 4 – 4 = 0 Solving with algebra leads to: x = 4 The results then are: x = 4z = -2y = -2

To Conclude Equations of the form ax+by+cz=h, who have x, y, and z unknown can be solved in the following way: With (n) unknowns and (n) equations, decide on a variable to exclude from an upcoming equation that will have (n-1) unknowns. Now choose two equations that will be added to eliminate the chosen variable

To Conclude Multiply one variable’s coefficient, of one equation, with the coefficient of the same variable in the other equation, and do the same for the other, except multiplying by the opposite of the coefficient. (ex. 5x and 2x, multiply 5x by 2 and 2x by -5) Now add them and you will have eliminated a variable

To Conclude Continue this process until you have one equation one unknown. Known solve for the variable and use the result as a substitution for the equations with more than one unknowns.